2014
DOI: 10.1016/j.psychres.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Altered time-perception performance in individuals with high schizotypy levels

Abstract: The possibility of altered time-perception in high schizotypy scorers, as postulated through previous differences shown in performance between high and low scorers in schizotypy on schedules of reinforcement with temporal elements, was examined using a series of retrospective timing tasks. Three stimuli ratio manipulations were made across two experiments, and, using an adjusted version of the bisection-point method for data analysis, results showed that high scorers on the unusual experiences subscale of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(81 citation statements)
references
References 57 publications
1
13
1
Order By: Relevance
“…The lack of any analogous relationship between UnEx and suprasecond timing performance might be accounted for by several explanations. First, it is of course plausible that no relationship exists between these variables in the suprasecond domain, and that the results of Experiment 1 are a product of largely independent subsecond timing mechanisms (this would be consistent with the combined findings of Reed & Randell, [ 43 ] and Sarkin et al, [ 42 ]). This explanation would suggest that individuals who show high degrees of UnEx might also be expected to manifest subtle perturbations in other domains associated with the same underlying (most notably, cerebellar [ 69 ]) networks, such as perceptual decision-making and motor co-ordination [ 76 , 77 ]…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The lack of any analogous relationship between UnEx and suprasecond timing performance might be accounted for by several explanations. First, it is of course plausible that no relationship exists between these variables in the suprasecond domain, and that the results of Experiment 1 are a product of largely independent subsecond timing mechanisms (this would be consistent with the combined findings of Reed & Randell, [ 43 ] and Sarkin et al, [ 42 ]). This explanation would suggest that individuals who show high degrees of UnEx might also be expected to manifest subtle perturbations in other domains associated with the same underlying (most notably, cerebellar [ 69 ]) networks, such as perceptual decision-making and motor co-ordination [ 76 , 77 ]…”
Section: Discussionsupporting
confidence: 73%
“…Timing performance was correlated with O-LIFE subscale scores to investigate whether distinct profiles of schizotypy are associated with different patterns of duration estimation. On the basis of previous research [ 15 , 43 ], we were particularly interested in whether the Unusual Experiences (UnEx) subscale could be used to identify distinct patterns of temporal judgement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that individuals with schizotypy were impaired in time perception and processing, they tend to judge "long" for shorter durations (Randell, Ranjith-Kumar, Gupta, & Reed, 2009;Reed & Randell, 2014). Based on the aforementioned findings, we may speculate that the abnormal time perception in individuals with schizotypy may be one of the factors contributed to their devaluing of delayed rewards.…”
Section: Discussionmentioning
confidence: 55%